Kje so meje? - Radi Buh, Maša (Amfiteater (Ljubljana), 2024)
The paper takes as its starting point the relationship between “cancel culture” – and its related political correctness – and comedy. It articulates this relationship in more detail and places it in a sociopolitical context. Theories of comedy, the comic and humour highlight two different interpretations or functions of these genres: On the one hand, it can be a tool of social normativity, disciplining those parts of society that deviate from fictional norms through humour directed against them. On the other hand, it can also oppose such systems by revealing through comedy that “the emperor is indeed naked”. The history of cancel culture has its roots in the historical social interactions of Black Americans, which were comically oriented. An undertone of comedy also marked the initial emergence of the term, which first appeared on Twitter in tweets by Black Americans in 2014. However, only as it spread to other social groups and entered popular culture did it take on its current meaning, with the aim of withdrawing public support from individuals, brands, etc., for perceived inappropriate or controversial behaviour. The view that comedy, in whatever form, is absolutely “sacred” and “untouchable” is merely a consequence of the bourgeois conception of the autonomy of art, which denies it any political charge and attempts to conceal the social power relations at work within comic procedures.
Keywords: cancel culture; comedy; cultural critique; humor theories; incongruity theory; komedija; kultura ukinjanja; kulturna kritika; teorija humorja; teorija neskladja